Between Ambition and Reality: Indonesia's One Channel System as an Instrument of National Interest in Malaysia - RIfky, Muhammad Alif; Dewi, Anggia Utami; Darmawan, Wawan Budi (Nation State: Journal of International Studies, 2025)
This article examines Indonesia's One Channel System (OCS) as a strategic labor migration policy. Grounded in a qualitative content analysis of policy documents and bilateral agreements, the study moves beyond a descriptive account to offer a critical evaluation of the OCS. It utilizes Michael G. Roskin’s theory of National Interest as a foundational framework for understanding the state’s motivations. Still, it enriches this with complementary lenses from the International Relations literature, including migration governance, labor diplomacy, and human security. The findings affirm that the OCS serves as a key instrument of Indonesian statecraft, advancing national security, securing economic interests through remittance formalization, and enhancing international prestige. However, the analysis reveals that significant challenges severelly constrain the policy’s effectiveness. These include a persistent lack of bilateral cooperation from Malaysia, critical on-the-ground implementation gaps, and the unintended risk of state overreach. A fundamental disconnect between the policy’s top-down objectives and the lived realities and agency of migrant workers. The study concludes that while the OCS is a vital assertion of regulatory sovereignty, its success is contingent on bridging the gap between state-centric interests and worker-centric protection. It suggests that future policy must prioritize legally binding bilateral enforcement and address deep-rooted implementation failures.